THE SIGNIFICANCE OF OIBEK'S "CHILDHOOD" IN THE EDUCATION OF YOUTH (Conference Zone, 2022)
The article provides a scientific analysis of Oybek's story "Childhood" and its role in the education of young people. The protagonist of this work is Oybek himself, the play shows various interesting events in Oybek's youth and historical events of that period.